Ghd7.1 improves eating quality by reducing grain protein content in rice - Kaijing Yuan; Yage Dong; Wenqiang Sun; Liting Zhang; Muhammad Asif; Sibin Yu (Crop Journal)
Protein content plays a crucial role in determining the eating and cooking quality of rice. However, the genetic and molecular basis underlying grain protein content remains to be elucidated. In this study, we identified a genomic region associated with grain protein content in rice chromosome segment substitution lines containing the flowering gene Ghd7.1, which reduced grain protein content by repressing the transcription of the gene OsAAP6. Knockout of Ghd7.1 increased grain protein content and decreased the eating and cooking quality of rice. Introduction of the functional haplotype of Ghd7.1 into two elite rice cultivars reduced their protein content and increased their eating quality and grain yield with no effect on the regulation of flowering time. Ghd7.1 might be used for regulating the protein content and improving the eating quality of rice varieties.